Anaemia is not a risk factor for progression of acute kidney injury: a retrospective analysis. Issue 1 (December 2016) - Powell-Tuck, Jonah; Crichton, Siobhan; Raimundo, Mario; Camporota, Luigi; Wyncoll, Duncan; Ostermann, Marlies
Abstract Background In hospitalised patients, anaemia increases the risk of developing acute kidney injury (AKI). Our aim was to determine whether anaemia also has an impact on the risk of progression from early AKI to more severe AKI in critically ill patients. Methods We retrospectively analysed the data of patients admitted to the adult intensive care unit between 2007 and 2009 who had AKI I as per the AKI Network classification, and who had undergone haemodynamic monitoring within 12 h of AKI I. We collected baseline characteristics, severity of illness, haemoglobin (Hb), and haemodynamic parameters in the first 12 h of AKI I and differentiated between patients who progressed to AKI III and those who did not. Univariate and multivariate logistic regression analyses were used to identify risk factors for progression. Associations between Hb, arterial oxygen saturation and cardiac index were explored by receiver operating characteristic curve analysis. Results Two hundred and ten patients (median age 70 years, 68 % male) underwent haemodynamic monitoring within 12 h of AKI I; 85 (41.5 %) progressed to AKI III. The proportion of patients with underlying cardiac disease was significantly higher among progressors versus non-progressors (58 % vs 34 %, respectively;p  = 0.001). On the first day of AKI I, progressors had a significantly higher Sequential Organ Failure Assessment score (9 vs 8;p  < 0.001), lower cardiac index (median 2.6 vs 3.3 L/min/m2 ;p  < 0.001), higher arterial lactate (2 vs 1.6 mmol/L;p  < 0.001), higher central venous pressure (16 vs 13;p  = 0.02), lower mean arterial blood pressure (median 71 vs 74 mmHg;p  = 0.01) and significantly higher requirement for cardiovascular and respiratory support, but there was no difference in Hb concentration (median 96 g/L in both groups). Multivariable regression analysis showed that heart disease, need for mechanical ventilation, arterial lactate, Sequential Organ Failure Assessment score, central venous pressure and cardiac index on first day of AKI I were independently associated with progression to AKI III. There was no significant difference in the risk of progression between patients with Hb ≤ or >80 g/L, and ≤ or >100 g/L on day of AKI I. Conclusions In critically ill patients with AKI stage 1, anaemia was not associated with an increased risk of progression to more severe AKI.